A novel continuous colour mapping approach for visualization of facial skin hydration and transepidermal water loss for four ethnic groups. (25th August 2015) - Voegeli, R.; Rawlings, A. V.; Seroul, P.; Summers, B.
Synopsis: Objectives: The aim of this exploratory study was to develop a novel colour mapping approach to visualize and interpret the complexity of facial skin hydration and barrier properties of four ethnic groups (Caucasians, Indians, Chinese and Black Africans) living in Pretoria, South Africa. Methods: We measured transepidermal water loss (TEWL) and skin capacitance on 30 pre‐defined sites on the forehead, cheek, jaw and eye areas of sixteen women (four per ethnic group) and took digital images of their faces. Continuous colour maps were generated by interpolating between each measured value and superimposing the values on the digital images. Results: The complexity of facial skin hydration and skin barrier properties is revealed by these measurements and visualized by the continuous colour maps of the digital images. Overall, the Caucasian subjects had the better barrier properties followed by the Black African subjects, Chinese subjects and Indian subjects. Nevertheless, the two more darkly pigmented ethnic groups had superior skin hydration properties. Subtle differences were seen when examining the different facial sites. Conclusions: There exists remarkable skin capacitance and TEWL gradients within short distances on selected areas of the face. These gradients are distinctive in the different ethnic groups. In contrast to other reports, we found that darkly pigmented skin does not always have a superior barrier function and differences in skin hydration values are complex on the different parts of the face among the different ethnic groups. Abstract : We developed a novel color mapping approach to visualize and interpret the complexity of facial skin hydration and barrier properties of four ethnic groups (Chinese, Caucasians, Indians, Black Africans). Skin capacitance (top row) and transepidermal water loss (TEWL) (bottom row) were measured on 30 predefined sites on the face and digital images were taken. Continuous color maps were generated by interpolating between each measured value and superimposing the values on the digital images revealing remarkable skin capacitance and TEWL gradients within short distances on selected areas of the face.